2013
DOI: 10.1159/000353464
|View full text |Cite
|
Sign up to set email alerts
|

Rise and Persistence of Animal Polyploidy: Evolutionary Constraints and Potential

Abstract: The past decade has witnessed a tremendous increase in interest in polyploidy, which may partly be related to the development of new powerful genetic and genomic tools. These have provided numerous insights into mainly genetic and genomic consequences of polyploidy, dramatically improving our understanding of the dynamics of the polyploidization process and its importance as a mechanism in animal evolution. In contrast, several other aspects of polyploidization, such as physiology, ecology and development, hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 144 publications
(204 reference statements)
1
50
0
Order By: Relevance
“…Recent polyploids have been identified in fishes and amphibians (Choleva and Janko, 2013;Gui and Zhou, 2010;Otto, 2007;Song et al, 2012) and some diploidized tetraploid species have been demonstrated in some teleost fish lineages including cyprinids, catostomids, and salmonids (Allendorf and Thorgaard, 1984;Collares-Pereira et al, 2013;Gui and Zhou, 2010;Yang and Gui, 2004), but the two recent rounds of polyploidy have been documented only in the polyploid gibel carp. Recent genome-wide studies have confirmed that the problem of genetic incompatibility raised by polyploidy may be resolved by the accumulation of diverse mutational changes to form a stable chimerical and diploidized genome (Buggs et al, 2011;Chen and Ni, 2006;Louis et al, 2012;Tate et al, 2009).…”
Section: Evolutionary Consequences Of Polyploidy In Gibel Carpmentioning
confidence: 99%
“…Recent polyploids have been identified in fishes and amphibians (Choleva and Janko, 2013;Gui and Zhou, 2010;Otto, 2007;Song et al, 2012) and some diploidized tetraploid species have been demonstrated in some teleost fish lineages including cyprinids, catostomids, and salmonids (Allendorf and Thorgaard, 1984;Collares-Pereira et al, 2013;Gui and Zhou, 2010;Yang and Gui, 2004), but the two recent rounds of polyploidy have been documented only in the polyploid gibel carp. Recent genome-wide studies have confirmed that the problem of genetic incompatibility raised by polyploidy may be resolved by the accumulation of diverse mutational changes to form a stable chimerical and diploidized genome (Buggs et al, 2011;Chen and Ni, 2006;Louis et al, 2012;Tate et al, 2009).…”
Section: Evolutionary Consequences Of Polyploidy In Gibel Carpmentioning
confidence: 99%
“…At this point, there is little evidence that they are. Well-documented cases are limited to parasitic wasps and thrips, and there are many parthenogenetic lineages in which no intracellular bacteria have been detected [56,57]. There are some cases in groups other than parasitic wasps in which parthenogenetic lineages are Wolbachia or Cardinium infected while related sexual lineages are not [58,59].…”
Section: (A) Parthenogenesismentioning
confidence: 99%
“…This is due to environmental factors, mainly external fertilization and a weak ethological isolating mechanism (Stolzenberg et al, 2009). Fish of the family Cobitidae, especially the Cobitis taxa, are an interesting object to study hybridization and subsequent polyploidization processes (Saitoh et al, 2010;Choleva & Janko, 2013;Choleva et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The loaches of Cobitis in Central Europe occur mainly in mixed diploid-polyploid populations, in which individuals of spined loach C. taenia Linnaeus, 1758 and/or Danubian spined loach C. elongatoides Bacescu & Maier, 1969 co-exist with their diploid and polyploid hybrids (Boroń, 2003;Choleva & Janko, 2013;Choleva et al, 2014). Both of these species are small-sized, bottom dwelling fish.…”
Section: Introductionmentioning
confidence: 99%